Improving best practice for patients receiving hospital discharge letters: a realist review protocol - Weetman, Katharine (BMJ Open, 2017)
INTRODUCTION: Discharge documents are important for transferring information from hospitals to the referring clinician; in the UK and many countries, this is often the patient’s general practitioner or family physician. However, patients may or may not receive their discharge letters, and whether patients should routinely receive discharge letters remains unclear. METHODS AND ANALYSIS: The review will consolidate evidence on patients receiving discharge letters through the theory-driven approach of a realist review. The review will be conducted systematically and seek to explain how, why, for whom and in what contexts does this practice ‘work’. The review will specifically explore whether there are benefits of this practice and if so what are the important contexts for triggering the mechanisms associated with these outcome benefits. Negative effects will also be considered. Several steps will occur: devising initial rough programme theory, searching the evidence, selecting relevant documents, extracting data, synthesising and finally programme theory refinement. As the process is viewed as iterative, this cycle of steps may be repeated as many times as is necessary to reach theoretical saturation and may not be linear. The initial programme theory will be tested and refined throughout the review process and by stakeholder involvement of National Health Service (NHS) policy makers, practitioners and service users. ETHICS AND DISSEMINATION: Formal ethical review is not required. The resulting programme theory is anticipated to explain how the intervention of patients receiving written discharge communication may work in practice, for whom and in what contexts; this will inform best practice of patients receiving discharge communication. The review findings will be disseminated in a peer-reviewed journal and presentations and discussions with relevant organisations and stakeholders. While the review will be from the perspective of the UK NHS, its findings should be relevant to other healthcare systems. PROSPERO REGISTRATION NUMBER: CRD42017069863.